Orientalisme Vs Oksidentalisme: Benturan dan Dialogisme Budaya Global - Rohanda Rohanda; Dian Nurrachman (Center for Research and Development of Religious Literature and Heritage, Agency for Research and Development and Training, Ministry of Religious Affairs of the Republic of Indonesia, 2017)
Imperialism and colonialism have spawned research centers that examine the parts of the world that they control. Through these centers, orientalists work to discuss, write, produce and perform the Eastern world on the stage of Western culture. Authenticity, exoticism and grandeur of the East are dismantled, stripped down, doubted and elusive. Through orientalist goggles, the East is produced as a